Geotouristic Coastal Itinerary in the South Coast of Paraíba (Northeast of Brazil) - Luciano Pereira; Arilde Alves (Geoconservation Research)
Geotouristic itineraries are important tools for the dissemination of geosciences because they work as outdoor field classes for teaching about the physical phenomena associated with the landscape in question, including the cultural one. Coastal environments are areas of great geotouristic potential precisely for this natural dynamics that give them its scientific value. The South coast of the State of Paraíba belongs to the geomorphologic unit of Plains and Coastal Tablelands, having direct relation with ancient tectonic movements, generated during the drift of the South American and African Plates, added to Cenozoic tectonic events. This article proposes a geotouristic itinerary that includes seven places of geotouristic interest. As a methodological path, the phases were the bibliographic research about the physical and cultural aspects of the area, an inventory of places of interest and their quantitative assessment. The places of interest are Amor Rock, Tombolo of Coqueirinho, Canyon of Coqueirinho, Cones of Dejection of Coqueirinho, Coqueirinho Structural High, Tambaba Beach and ‘Maceió’ of Mucatu. The existence of interpretative trails assigns a new function, now from the geotouristic point of view, to the itineraries, as they enrich the experience of tourists, to whom is given the opportunity of knowing the abiotic heritage and the cultural heritage from another perspective, apart from enhancing their environmental awareness. The geotouristic itineraries also serve to promote geotourism as an asset, inserting in the traditional tourist context information about the previously forgotten abiotic environment. The 'sun and sea' is the main tourist attraction of the region, allied in a secondary level to a rich history and culture that neglects the latent geotouristic potential. Therefore, mass tourism will be promoted for a niche tourism, becoming more sustainable under the environmental bias.